2018
DOI: 10.3390/e20120901
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Image Encryption Scheme Based on Collatz Conjecture

Abstract: Image encryption methods aim to protect content privacy. Typically, they encompass scrambling and diffusion. Every pixel of the image is permuted (scrambling) and its value is transformed according to a key (diffusion). Although several methods have been proposed in the literature, some of them have been cryptanalyzed. In this paper, we present a novel method that deviates the traditional schemes. We use variable length codes based on Collatz conjecture for transforming the content of the image into non-intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Aashiq et al [ 14 ] presented an image encryption method based on chaotic attractors; on the frequency domain they used the integer wavelet transform to encrypt the image while on the spatial domain they used the DNA sequence. Ballesteros et al [ 15 ] presented a novel method that deviated from traditional schemes, in which variable-length codes based on the Collatz conjecture were used to transform the content of the image into unintelligible audio. Moreover, Ouyang et al [ 16 ] proposed a color image encryption method using the memristive hyperchaotic system and DNA encryption, and Zhu et al [ 17 ] reported an image encryption algorithm based on a matrix of Kronecker products and DNA operations over finite fields.…”
Section: Introductionmentioning
confidence: 99%
“…Aashiq et al [ 14 ] presented an image encryption method based on chaotic attractors; on the frequency domain they used the integer wavelet transform to encrypt the image while on the spatial domain they used the DNA sequence. Ballesteros et al [ 15 ] presented a novel method that deviated from traditional schemes, in which variable-length codes based on the Collatz conjecture were used to transform the content of the image into unintelligible audio. Moreover, Ouyang et al [ 16 ] proposed a color image encryption method using the memristive hyperchaotic system and DNA encryption, and Zhu et al [ 17 ] reported an image encryption algorithm based on a matrix of Kronecker products and DNA operations over finite fields.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, various encryption techniques that are dependent on chaos have been examined and broadly contemplated. Image encryption algorithms have been constructed based on a logistic and two-dimensional (2D) chaotic economic map [ 6 ], variable length codes that are based on Collatz conjecture [ 7 ], 2D discrete wavelet transform and Arnold mapping [ 8 ], logistic mapped convolution and cellular automata [ 9 ], cat map [ 10 ], 2D Chebyshev-sine map [ 11 ], 2D Sine Logistic modulation map [ 12 ], one-dimensional (1D) delay with linearly coupled Logistic chaotic map [ 13 ], a hyper-chaotic system that combines Dynamic Filtering, DNA computing, and Latin Cubes (DFDLC) [ 14 ], Arnold Transform followed by Qubit Random Rotation [ 15 ], 2D Baker’s map with diffusion process based on XORing [ 16 ], ant colony optimization [ 17 ], Chebyshev Map followed by Rotation Equation [ 18 ], an algorithm combining Julia fractal and Hilbert curve [ 19 ], four-dimensional (4D) hyper-chaotic nonlinear Rabinovich system [ 20 ], Josephus traversing and mixed chaotic map [ 21 ], 2D logistic-modulated-sine-coupling-logistic chaotic map [ 22 ], multiple permutation of pixels followed by the 2D Chebyshev function [ 23 ], chaos map with pixel permutation [ 24 ], improved hyperchaotic sequences [ 25 ], high-dimension Lorenz chaotic system with a perceptron model [ 26 ], rotation matrix bit-level permutation with block diffusion [ 27 ], and discrete Chirikov map with chaos-based fractional random transform [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concealing data in an inconspicuous way is called steganography [ 1 ] and is mainly used to communicate secretly. This attribute differentiates it from cryptography [ 2 , 3 ]—when information is encrypted, it cannot be read, but everyone knows of its existence. In steganography, the primary goal is undetectability of secret message.…”
Section: Introductionmentioning
confidence: 99%